2017
DOI: 10.1159/000477501
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Medical Management Reduces Risk of Disease Progression and Ischemic Events in Asymptomatic Carotid Stenosis Patients: A Long-Term Follow-Up Study

Abstract: Background and Purpose: To assess the effect of optimal medical management including atherosclerotic risk factor control on ischemic stroke (IS), transient ischemic attack (TIA), carotid revascularization (CRV), and progression of severity of carotid stenosis (PSCS) in patients with asymptomatic carotid artery stenosis (ACAS). Methods: We conducted a retrospective analysis of patients with ACAS (who had at least 3 serial carotid duplex ultrasounds) for incidence of IS, TIA, and PSCS. Results: Eight hundred six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…The results of the present study add up to 8.8% for lesions above 50% in patients with PAD, and 6.2% over 70%, which, to date, meet the few published findings, but with lower values when compared to published studies ranging from 5 to 24% in patients with PAD [11][12][13]. In the Present Review of Asymptomatic Carotid Stenosis (2020), the authors found 13.4% prevalence of moderate stenosis and 21.8% for severe stenosis [21].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results of the present study add up to 8.8% for lesions above 50% in patients with PAD, and 6.2% over 70%, which, to date, meet the few published findings, but with lower values when compared to published studies ranging from 5 to 24% in patients with PAD [11][12][13]. In the Present Review of Asymptomatic Carotid Stenosis (2020), the authors found 13.4% prevalence of moderate stenosis and 21.8% for severe stenosis [21].…”
Section: Discussionsupporting
confidence: 82%
“…We know that PAD is a systemic disease and that it represents a high-risk factor for cardiovascular events [8][9][10], and we have only a few studies addressing this association, with evidences for the prevalence of atherosclerotic disease, which is higher in patients with PAD than in patients without PAD [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…These factors have shown to reduce risk of ischemic events or progression of stenosis. 14,41 In specific cases, selected patients with high-risk stenosis (e.g. cerebral microembolization, intraplaque hemorrhage, echolucent plaque formation, silent embolic infarcts on brain imaging, or reduced cerebral blood flow reserve) should be considered for treatment with interventional methods.…”
Section: Discussionmentioning
confidence: 99%
“…1 This has recently been confirmed in 864 patients with 50-69% or 70-99% carotid artery stenosis. 21 Altogether, 4929 carotid ultrasound studies were performed on 1439 carotid arteries over 6.5 years. Ischaemic stroke/transient ischemic attack (TIA) and carotid revascularization occurred in 12.2% and progression of the stenosis in 21.5% of patients.…”
Section: Optimal Medical Managementmentioning
confidence: 99%
“…21 Altogether, 4929 carotid ultrasound studies were performed on 1439 carotid arteries over 6.5 years. Ischaemic stroke/transient ischemic attack (TIA) and carotid revascularization occurred in 12.2% and progression of the stenosis in 21.5% of patients. The quality of risk factors control were independent predictors for the stenosis progression or occurrence of stroke/TIA (Figure 1).…”
Section: Optimal Medical Managementmentioning
confidence: 99%